Training Design Development: The Practice Of Four Development Agencies In Malaysia - Ahmad, Asma (1994)

(untitled)
Efficient and effective training programmes are needed to produce competent workers in order to achieve the development goals of a country.Therefore, strategy-oriented , coordinated training designs are important to maximize the impact of the training activities. This study was conducted to identify the training design(s)and components employed by the training personnel of Malaysian Agricultural Research and Development Institute (MARDI ),the Federal Land Development Authority ( FELDA ),the Rubber Industry